Fanning the flames of brand love: The impact of the fan page and the mediating role of sense of brand community - Audria, Ulfi; Susan, Marcellia; Gomulia, Budiana (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
This conceptual paper explores the impact of fan pages on brand love and the mediating role of a sense of brand community. Given the increasing importance of social media in brand management, this paper employs deductive reasoning to explore the relationships between key variables with the aid of established theories and a new conceptual framework. The authors present a proposition that predicts the connections between constructs and explores fan pages' impact on brand love directly and indirectly via the mediating variable sense of brand community. The study highlights the benefits of fan pages in maintaining consumer-brand relationships and provides valuable insights for marketers to enhance firm performance through effective fan page strategies and improved customer experiences. This study adds to the literature on social media marketing and offers practical ways for companies to utilize fan pages and brand communities to foster brand love.